Study of vehicle movement In mixed traffic flow at signalised junctions - Ong, Wendy Xue-Ni (2014)
Singapore is one of the countries in the world with motorcycles found commonly on the road. As motorcycles are smaller in size with greater power-to-weight ratio, they tend to display certain unique movement characteristics that are difficult to model using conventional methodologies. Hence, this problem may result in inaccurate assessments of traffic performance in Singapore. Moreover, the safety of motorcyclists is often compromised by their riding behaviour on the road. In this project, investigation was done with heavy reliance on the micro-simulation modelling in PTV VISSIM 5.40. The research is based on the data collected via video recordings from three junctions in Singapore. Traffic volumes and signal timings of these junctions were extracted as data values for the modelling. A typical model of the junction was first established to investigate the movements of motorcycles in the simulation. It was found that existing models were unable to well reflect the unique behaviour of motorcycles in reality. Subsequently, a modified model was created with the inclusion of virtual lanes to account for the proportion of motorcycles travelling in between lanes. Additionally, the stop lines of these virtual lanes were extended beyond the normal stop lines to take into consideration for the shorter start-up time due to the higher power-to-weight ratio of motorcycles as well as the behaviour of them shuffling to the front of the queue during red signal phase. The desired outcome of this modification was to find out whether the behaviour of motorcycles travelling in between lanes and to the front of the queue would affect the average travel and delay time of vehicles passing through the signalised junctions. Two main conclusive points have been determined from this research project. First, it is found that vehicles take a shorter average travel time to pass through the junction using the modified model as compared to conventional model. This suggests that the conventional model is conservative in assessing traffic performance for the Singapore’s context. Secondly, results show that motorcycles travelling in between lanes reduce the average travel time and delay of vehicles passing through a signalised junction in Singapore as compared to them travelling in lanes. This implies that traffic performance could be enhanced if most motorcycles travel in between lanes.